Molecular mechanisms of pattern formation by the BRE enhancer of the Ubx gene. - Qian, S.; Capovilla, M.; Pirrotta, V. (The EMBO Journal, 1993)
The core activity of the Ubx gene enhancer BRE (bx region enhancer) is encoded within a 500 bp module. bx DNA outside this active module increases the level of expression, expands the expression into ventro-lateral ectoderm and partially stabilizes the late expression pattern. The products of the gap genes hb and tll and of the pair-rule gene ftz bind to the 500 bp BRE module and control directly its initial pattern of expression. ftz enhances expression in even-numbered parasegments within the correct spatial domain whose boundaries are set by hb and tll. In addition, en and twi products activate the enhancer, probably directly. en broadens the parasegmental stripe while twi cooperates with ftz to enhance expression in the mesoderm. Binding sites for the five regulators are closely clustered, often overlapping extensively with one another. In vitro, hb blocks the binding of ftz and can also displace ftz protein pre-bound to an overlapping site, suggesting that competitive binding and/or interference by hb sets the initial boundaries of the domain of expression. Our results also suggest that this interaction is short-range and the long distance interactions among different enhancers may depend on each enhancer's ability to complex with the promoter.